EFEKTIFITAS METODE PEMBELAJARAN MIND MAPPING TERHADAP HASIL BELAJAR MAHASISWA KEBIDANAN SEMESTER IV POLTEKKES KEMENKES YOGYAKARTA - Susilo Rini (Universitas Harapan Bangsa Purwokerto, 2009)
Background: effective learning methods are still less widely used diinstitusi midwifery education in particular, so many students who have difficulty in understanding,remembering and re mereviuw lesson, this causes the output was less than the maximum. Oneof the methods known learning effective in improving student learning outcomes are MindMapping, Wikimindmap (2008) says that Mind Mapping can improve the effectiveness oflearning up to 15%, so the need for research on the effectiveness of learning Mind Mappingmethods to improve student learning outcomes midwifery. Method: Experiment study with pretest-posttest design with control group. Locationof study at polytechnic Kemenkes Yogyakarta Programs Midwifery. The subjects were 60students have regular classes and extension classes of fourth semester taken by clusterrandom sampling. The type of data is primary data. Analysis of data using independentsample t-test with a significance of 0.05. Results: The t test showed a mean learning outcomes of students with learning MindMapping method was (3.47 Â± 1.252) whereas the average results of student learning with thelearning method for non Mind Mapping (2.27 Â± 0.785). T-count (4.448)> t-table (1.678) withÏ (0.003) <Î± (0.05). Keywords: Effectiveness, Learning Method, Mind Mapping, Learning Outcomes.